Gender differences in preferences for health-related absences from work - Daniel Avdic; Per Johansson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
Women are on average more absent from work for health reasons than men. At the same time, they live longer. This conflicting pattern suggests that part of the gender difference in health-related absenteeism arises from differences between the genders unrelated to actual health. An overlooked explanation could be that men an women's preferences for absenteeism differ, for example because of gender differences in risk preferences. These differences may originate from the utility-maximizing of households in which women's traditional dual roles influence household decisions to invest primarily in women's health. Using detailed administrative data on sick leave, hospital visits and objective health measures we first investigate the existence of gender-specific preferences for abstenteeism and subsequently test for the household investment hypothesis. We find evidence for the existence of gender differences in preferences for absence from work, and that a non-trivial part of these preference differences can be attributed to household investments in women's health.
Keywords: I13; J22; D13; 330; sickness absence; gender norms; health investments